Examining the Relationships between Primary School Principals’ Power Styles and Teachers’ Professional Behaviors - KOŞAR, Serkan; KILINÇ, Ali Çağatay; ER, Emre; ÖĞDEM, Zeki; SAVAŞ, Gökhan (Alberta Journal of Educational Research, 2015)
The purpose of this study was to examine the relationship between primary school principals’ power styles and teacher professionalism. A total of 264 teachers employed in 10 primary schools in Kastamonu, Turkey, participated in this study. Kosar’s (2008) “Power Styles Scale,”and the “Teacher Professionalism Scale”—originally developed by Tschannen-Moran, Parish, and DiPaola (2006), and adapted into Turkish by Cerit (2013)—were used to gather data. The mean, standard deviation, correlation, and regression analyses were calculated to evaluate the data. The results revealed that teacher professionalism was positively and significantly related to personality and reward power, while being negatively and significantly correlated with legitimate and coercive power. The findings also showed that the power styles of school principals significantly predicted teacher professionalism. The outcomes of the study are discussed with respect to improving teacher self-efficacy. L’objectif de cette recherche était d’étudier le rapport entre les styles ou processus du pouvoir des directeurs d’écoles primaires et le professionnalisme des enseignants. À cette étude ont participé 264 enseignants travaillant dans 10 écoles primaires à Kastamonu, en Turquie. L’article « Power Styles Scale » de Kosar (2008) et la « The Teacher Professionalism Scale » d’abord développée par Tschannen-Moran, Parish et DiPaola, et ensuite adaptée en turque par Cerit (2013), ont servi à la cueillette de données. Pour évaluer les données, on a calculé la moyenne, l’écart type, la corrélation et les analyses de régression. Les résultats indiquent que le professionnalisme des enseignants présente une corrélation positive significative avec le pouvoir du référent et le pouvoir de récompense, et une corrélation négative significative avec le pouvoir légitime et le pouvoir coercitif. Les résultats indiquent également que le style du pouvoir des directeurs est un prédicteur fiable du professionnalisme des enseignants. On discute des résultats de l’étude dans l’optique d’améliorer l’auto-efficacité des enseignants.